Reviving Halal Tourism After COVID-19 In Indonesia - Aldo Raventio Adam (Badan Pelaksana Rinjani-geopark Rinjani Lombok, 2023)
OVID-19 has shut down various sectors of human life, including the possibility of traveling from place to place. Indonesia, also affected by COVID-19, experienced a significant decrease in foreign exchange due to the decline in tourism sector activities. Indonesia, also known as a country with a majority Muslim population, is usually the leading destination for halal tourism, with the number of Muslim tourists as much as 18.24% of all tourists who come to Indonesia. However, as the impact of COVID-19, the number of Muslim tourists from other countries declined dramatically in 2020, along with the drop in foreign flights. Domestic Muslim tourists also witnessed a downturn. Indonesia was ranked as the best halal tourism country in 2019. As COVID-19 hit hard, Indonesia became the 4th number in the ranking. But in 2022, Indonesia became the second-best country with halal tourism. To revive the tourism sector, many integrated programs for implementing health protocols are required to enhance the economy in the tourism industry, particularly halal tourism. This article aims to find out the strategy for Indonesia to revive the halal tourism sector during COVID-19. The method used in this study is a qualitative method with data collection techniques used in the literature study. The study results stated that the strategy to revive the halal tourism sector from the COVID-19 pandemic consists of 2 stages, recovery (Preparing Destinations Industry, Institutions, and Marketing) and normalization (Promote Dimensions of Halal Tourism). The GMTI of Indonesia proves that it increased the communication component, especially the destination marketing aspect. The enthusiastic community expects the implementation of this program to return to reinvigorate the tourism sector, especially halal tourism.